Analysis of corner kicks in relation to match status in the 2006 World Cup - Sainz de Baranda, P.; Lopez-Riquelme, D. (European Journal of Sport Science, 2012)
The aim of this study was twofold: to provide a quantitative analysis of corner kicks during the 2006 World Cup and to examine the effect of match status on corner kicks. Through the elaboration of a category system and following an observational methodology, we performed an analysis of all corner kicks (n = 653) in the 64 matches in the 2006 World Cup held in Germany. Matches were divided into sections according to evolving match status (whether the team was winning, n = 144; losing, n = 171; or drawing, n = 338). Using an observational methodology the following performance indicators were analysed: type of corner kick, scoring area, effectiveness, subsequent play, part of the body used to shoot, goal zone, number of players defending the goalposts, and defence tactics. The results obtained showed that: a) in relation to kick modality, teams perform more short corners and take more short kicks and outswing corner kicks when winning. On the other hand, teams perform more outstep and inswing corner kicks when drawing and losing; b) In relation to the scoring area, teams perform more shots that head toward the semicircle placed by the penalty area or do not use the centre when winning. However, teams head their s'hots toward the first and the second goalpost when drawing and losing; c) In relation to defence, when teams that are winning perform the corner kick, the defending teams tend to have fewer players defending the goal line; d) No significant statistical association was observed for the following performance indicators: effectiveness, subsequent play, part of the body used to shoot, goal zone, and defensive system.